Risk of bias and methodological issues in randomised controlled trials of acupuncture for knee osteoarthritis: A cross-sectional study - Jia, P.; Tang, L.; Yu, J.; Lee, Andy; Zhou, X.; Kang, D.; Luo, Y.; Liu, J.; Sun, X. (BM J Group, 2018)
© Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2018. All rights reserved. No commercial use is permitted unless otherwise expressly granted. Objective To assess risk of bias and to investigate methodological issues concerning the design, conduct and analysis of randomised controlled trials (RCTs) testing acupuncture for knee osteoarthritis (KOA). Methods PubMed, EMBASE, Cochrane Central Register of Controlled Trials and four major Chinese databases were searched for RCTs that investigated the effect of acupuncture for KOA. The Cochrane tool was used to examine the risk of bias of eligible RCTs. Their methodological details were examined using a standardised and pilot-Tested questionnaire of 48 items, together with the association between four predefined factors and important methodological quality indicators. Results A total of 248 RCTs were eligible, of which 39 (15.7%) used computer-generated randomisation sequence. Of the 31 (12.5%) trials that stated the allocation concealment, only one used central randomisation. Twenty-five (10.1%) trials mentioned that their acupuncture procedures were standardised, but only 18 (7.3%) specified how the standardisation was achieved. The great majority of trials (n=233, 94%) stated that blinding was in place, but 204 (87.6%) did not clarify who was blinded. Only 27 (10.9%) trials specified the primary outcome, for which 7 used intention-To-Treat analysis. Only 17 (6.9%) trials included details on sample size calculation; none preplanned an interim analysis and associated stopping rule. In total, 46 (18.5%) trials explicitly stated that loss to follow-up occurred, but only 6 (2.4%) provided some information to deal with the issue. No trials prespecified, conducted or reported any subgroup or adjusted analysis for the primary outcome. Conclusion The overall risk of bias was high among published RCTs testing acupuncture for KOA. Methodological limitations were present in many important aspects of design, conduct and analyses. These findings inform the development of evidence-based methodological guidance for future trials assessing the effect of acupuncture for KOA.